The prognostic role of cardiac and inflammatory biomarkers in extubation failure in patients with COVID-19 acute respiratory distress syndrome - Carline N. L. Groenland; Adinde H. Siemers; Eric A. Dubois; Diederik Gommers; Leo Heunks; Evert-Jan Wils; Vivan J. M. Baggen; Henrik Endeman (Annals of Intensive Care)
Abstract Background Extubation failure is associated with an increased morbidity, emphasizing the need to identify factors to further optimize extubation practices. The role of biomarkers in the prediction of extubation failure is currently limited. The aim of this study was to investigate the prognostic value of cardiac (N-terminal pro–B-type natriuretic peptide (NT-proBNP), High-sensitivity Troponin T (Hs-TnT)) and inflammatory biomarkers (Interleukin-6 (IL-6) and Procalcitonin (PCT)) for extubation failure in patients with COVID-19 Acute Respiratory Distress Syndrome (C-ARDS). Materials and methods In this single-center retrospective cohort study, patient characteristics and laboratory measurements were extracted from electronic medical records. Patients were eligible for inclusion if they were extubated after mechanical ventilation. The primary endpoint was extubation failure, defined as the need for reintubation or death within the next seven days after extubation, regardless of whether post-extubation respiratory support was used. Uni- and multivariable logistic regression was performed to investigate the association between biomarkers and extubation failure. Biomarkers were log2 transformed. Results Of the 297 patients included, 21.5% experienced extubation failure. In univariable analysis, NT-proBNP (OR 1.24, 95% CI 1.06–1.47), Hs-TnT (OR 1.72, 95% CI 1.37–2.19) and PCT (OR 1.38, 95% CI 1.16–1.65) measured on the day of extubation were significantly associated with extubation failure. After multivariable adjustment for clinical variables (age, duration of mechanical ventilation, SOFA score), Hs-TnT was the only biomarker that was independently associated with extubation failure (adjusted OR 1.38, 95% CI 1.02–1.90). Patients with both elevated Hs-TnT (≥ 14 ng/mL) and elevated PCT (≥ 0.25 ng/mL) carried the highest risk of extubation failure (46%), while in patients with normal Hs-TnT and PCT values, only 13% experienced extubation failure. Conclusions Hs-TnT, NT-proBNP and PCT measured on the day of extubation are associated with extubation failure in mechanically ventilated patients with C-ARDS. Since Hs-TnT is the only biomarker that is independently associated with extubation failure, Hs-TnT could offer additional objective measures for assessing readiness for extubation. Future studies should focus on an integrative approach of biomarkers combined with relevant clinical factors to predict extubation failure.